IDENTIFYING FACTORS DETERMINING PILGRIMS DELIGHT AND INVESTIGATING THEIR ABILITY TO PREDICT IN VRINDAVAN CITY OF NORTH INDIA - Amitabh Mishra , Ashutosh Singh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The study in hand applied exploratory factor analysis on the survey data to determine major factors that contributed in the pilgrim delight in Vrindavan city of North India. Total 568 pilgrims were interviewed in face to face personal interview on the most sacred places of Vrindavan city such as Banke Bihari temple, ISSKCON temple, etc. The study extracted the data using principle component analysis and varimax rotation method. Total five factors which determined pilgrims’ delights were identified and named as basic facilities, conveniences, public, meal, and protection. Further, application of linear regression analysis found a significant influence of all identified factors in the pilgrims delight and, found that identified factors were able to predict pilgrim delights in Vrindavan city of North India.